2023
DOI: 10.1371/journal.pone.0280741
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lipid-lowering therapies on the pro-inflammatory and anti-inflammatory properties of vascular endothelial cells

Abstract: Atherosclerosis and cardiovascular events can be prevented, or treated, using statin therapy, either alone or in combination with ezetimibe. Chronic inflammation, vascular proliferation, and the development of atherosclerosis are also influenced by 25-hydroxycholesterol (25-OHC). The aim of the study was to compare the direct pleiotropic effects of two commonly-used statins (atorvastatin, rosuvastatin), ezetimibe, and their combinations, on the mRNA expression of pro-inflammatory IL1β, IL-18 and IL-23 and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that ezetimibe lacked obvious pleotropic effects compared to statins. 27 In contrast to many experiments confirming the pleiotropic effect of statins, there is still insufficient evidence of the pleiotropic effect of ezetimibe. 28 Similarly, our data showed that portal hypertension and hyperdynamic circulation could not be reversed by 4 weeks of ezetimibe treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that ezetimibe lacked obvious pleotropic effects compared to statins. 27 In contrast to many experiments confirming the pleiotropic effect of statins, there is still insufficient evidence of the pleiotropic effect of ezetimibe. 28 Similarly, our data showed that portal hypertension and hyperdynamic circulation could not be reversed by 4 weeks of ezetimibe treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies aiming to better deciphering these 25-HC/EC interactions used human umbilical vein ECs or pulmonary ECs and confirmed that high concentrations of 25-HC have deleterious effect on these cells and affects endothelial barrier permeability. Thus, treatment of human umbilical vein ECs with 25 μM of 25-HC decreases the cell index ( 108 , 109 ) and promotes production of a long list of inflammatory molecules (IL1β, IL-18, IL-23, EBI-3, IL-12, IL-35, TNF-α, and IL-6) or molecules involved in cell growth or immune responses (ICAM-1, MCP-1, VEGF) by ECs ( 80 , 109 , 110 ). On the contrary, production of anti-inflammatory molecules TGF-β, IL-10, and IL-37 is decreased ( 109 ).…”
Section: Effects Of 25-hc On Vascular Ec and Epmentioning
confidence: 99%
“…On the contrary, production of anti-inflammatory molecules TGF-β, IL-10, and IL-37 is decreased ( 109 ). These downregulation or upregulations are reverted by several drugs including rosuvastatin, ezetimibe, rivaroxaban, and atorvastatin, all known to also targeting the cholesterol metabolism ( 109 , 110 , 111 ). As mentioned previously, 25-HC increase provokes a loss of the lung EC barrier integrity by disorganizing VE-cadherin assembly ( 54 ).…”
Section: Effects Of 25-hc On Vascular Ec and Epmentioning
confidence: 99%
“…They also encompass anti-inflammatory effects that inhibit cell proliferation, reduce the aggregation of inflammatory cells, and limit the secretion of pro-inflammatory cellular factors. Furthermore, statins have shown a pronounced impact on plaque stabilization and reduction, an effect considered to be linked to their anti-inflammatory capabilities [62][63][64].…”
Section: The Pleiotropic Effect Of Lipid-lowering Therapy After Acute...mentioning
confidence: 99%
“…In summary, the pleiotropic effects of statins contribute significantly to their cardioprotective role following ACS, offering benefits beyond lipid lowering. These effects include improving endothelial function, reducing vascular inflammation, and mitigating platelet activity, all of which are vital in reducing the incidence of periprocedural cardiac myonecrosis and the overall burden of cardiovascular disease post-PCI [61][62][63][64][65].…”
Section: The Pleiotropic Effect Of Lipid-lowering Therapy After Acute...mentioning
confidence: 99%